Crisis and philosophical practice in education (2020)
teaching of philosophy and philosophizing play a fundamental role in the training of human beings capable of thinking rationally, understanding, arguing, evaluating, reflecting, questioning, criticizing and proposing new alternatives to the understanding of knowledge and lived values, from the horizons of questions for foundations and in the organization of perspectives. The results of an adequate philosophical education are related to the training of autonomous, ethical subjects capable of living in democracy and who are self-conscious of the criteria of knowledge. In this approach, competencies and philosophical practice are defined, forming a heterogeneous group of abilities, experiences and values in which philosophy can be practiced in different places, situations and contexts. A more practical approach to philosophy makes students see this discipline more applicable, increases their taste for study and allows for dialogue and philosophical learning in other disciplines. The aim of this reflective work is to understand this philosophical learning as well as its contribution to the teaching of philosophy.